KI HADJAR DEWANTARA'S EDUCATION CONCEPT AND ITS RELEVANCE TO EDUCATION IN INDONESIA - Ilham Wahyudi; Firman; Riska Ahmad (Yayasan Citra Dharma Cindekia, 2021)
This paper is a scientific idea that aims to provide an overview of the educational concept of Ki Hajar Dewantrara and its relevance to education in Indonesia. In this article, we will discuss the concept of education itself. Ki Hadjar Dewantara views education as a driver for student development, namely education teaches to achieve change and benefit the surrounding environment. Purposeful education To promote the growth of character, which means the values of human life are carried out which are made into habits. character that is still grown and developed in students and has become a habit and self-awareness to be good. Based on this, this article was written with the aim of knowing how the concept of education and the relevance of education in Indonesia according to Ki Hajar Dewantara himself.